INFORMATION TECHNOLOGIES IN THE SYSTEM OF ORGANIZATION OF MONITORING OF QUALITY OF MATHEMATICS FUTURE TEACHERS PREPARATION - Oksana S. Turzhanska (Інформаційні технології і засоби навчання, 2011)
The relevance of the material stated in the article, is caused by the needs of professional education in realization of monitoring researches, because they are one of ways of expansion of access to European education and mobility of students. The effective functioning of monitoring in education requires the decisions of several tasks, among which  accumulation and conservation of information resources, and decision-making about quality of education. Monitoring software development in the process of professional preparation of future teachers of mathematics, considered in the article, consists of creation of database and realization of experimental model of monitoring in the system MATLAB. The created monitoring software assists its effective functioning.